Analisis Atribut Produk Terhadap Kepuasan Pelanggan Pada Ranu Original Store Jakarta Selatan - Annida Zahra; Anah Furyanah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Ranu Original Store specializes in authentic fashion and sneakers. It operates as a digital provider for school procurement, focusing on education-related products, rather than clothing or general retail goods as the name "Original Store" suggests, in South Jakarta. In collecting data, the author used qualitative descriptive analysis through observation and interviews. The research findings indicate that Ranu Original Store's product attributes (quality, features, design, brand, and packaging) have been implemented very well and meet the needs of the target market, both retail and institutional. Authenticity is the primary foundation of branding, successfully building a positive reputation. Customer satisfaction is significantly influenced by responsive service quality, staff empathy, and ease of transaction. Loyalty programs and feedback management are key to Ranu Original Store's success in maintaining customer retention, thus creating long-term, mutually beneficial relationships between sellers and buyers.